A case of juvenile dermatomyositis responding to methotrexate and steroid - Gunawan, Prastiya Indra; Saharso, Darto (Bangladesh Journal of Medical Science, 2018)
A 4-year-old patient presented with skin rash and muscle weakness. She was diagnosed with juvenile dermatomyositis based on Bohan and Peter criteria as well as laboratory testing. She received steroid and combined with methotrexate. The treatment resulted in a good response. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.675-677